PENGARUH KAPASITAS SUMBER DAYA MANUSIA,KOMITMEN ORGANISASI, PEMANFAATAN TEKNOLOGI INFORMASI DAN PENGENDALIAN INTERN AKUNTANSI TERHADAP NILAI INFORMASI PELAPORAN KEUANGAN PEMERINTAH DAERAH (STUDI PADA SATUAN KERJA PERANGKAT DAERAH PEMERINTAH PROVINSI MALUKU) - Sandanafu, Sally Paulina; Situmeang, Mis Fertyno (Politeknik Negeri Ambon, 2018)
This study aims to determine the effect of human resource capacity, organizational commitment, utilization of information technology and internal control accounting to the value of financial reporting information local government in the scope of SKPD Maluku province.This research is causal asosiatif research with quantitative approach, the sampling technique used is purposive sampling. The analysis used is multiple regression analysis (Multiple regression).The result of hypothesis test shows that variable of human resource capacity, organizational commitment and internal control of accountancy have a positive and significant influence to the value of local financial reporting information while the utilization of information technology has no positive effect to the financial information value of the area it is shown with coefficient value of 0.128 with significance level of 0.060.